The Effect of Clinical Rotation Students’ Quality of Service on Patient Satisfaction Through Service Experience at the Islamic Dental and Oral Health Education Hospital - Nurfitriana Besse; Fatmah Afrianty Gobel; Wardiah Hamzah; Masriadi Masriadi; Arni Rizqiani Rusydi; Hasriwiani Habo Abbas (Advances in Community Services Research, 2026)
Purpose: This study aims to analyze the effect of the quality of care provided by dental internship students on patient satisfaction through service experience as a mediating variable at RSIGMP UMI. Research Method: This study employed a quantitative cross-sectional design. The sample consisted of 308 respondents selected using purposive sampling. The independent variables included medical history, clinical examination, diagnosis and treatment plan, dental care procedures, and post-treatment education and instructions. Service experience was used as the mediating variable, and patient satisfaction as the dependent variable. Data were analyzed using path analysis. Results and Discussion: Medical history had a direct, positive, and significant effect on patient satisfaction. Clinical examination, diagnosis and treatment planning, dental treatment procedures, and post-treatment education and instructions did not have a significant direct effect on patient satisfaction. Medical history, diagnosis and treatment plan, treatment procedures, and post-treatment education and instructions had a significant effect on service experience, whereas clinical examination did not. Service experience mediated the effects of medical history, diagnosis and treatment plan, treatment procedures, and post-treatment education and instructions on patient satisfaction. Implications: Service experience plays a crucial role as a mediating mechanism between the quality of service provided by medical students and patient satisfaction. Efforts to improve service quality should emphasize communication, patient involvement, clear information, safe, comfortable procedures, and post-treatment education. Originality: provide the clear explanation regarding the original of your research.